Integrated Lens Antennas - Boriskin, A. V.; Sauleau, R.; Costa, J. R.; Fernandes, C. (Aperture antennas for millimeter and sub-millimeter wave applications, 2018)
This chapter presents the Integrated Lens Antenna (ILA) technology as it evolved since its introduction aiming to respond to the needs of emerging applications such as high-data-rate communication, intelligent transport, and mm-wave imaging. The topics covered include the ILA design concepts as well as the electromagnetic phenomena intrinsic to dielectric lenses that may affect ILA performance. The aspects of the ILA technology related to selection of the primary feeds, lens materials, and fabrication methods are also revised. A few practical examples are provided to illustrate the current and future trends of this technology.